The Relationship between Partner Support and the Choice of Long-Term Contraception in New KB Acceptors at the Lamunti Community Health Center UPT - Rochayati Rochayati; Reny Retnaningsih (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The use of long-acting contraceptive methods (MKJP) is an important strategy for reducing unintendedpregnancies and improving maternal and family health. However, contraceptive method choice is influenced notonly by individual factors but also by interpersonal factors within the family, particularly partner support. Thisstudy aims to analyze the relationship between partner support and long-acting contraceptive choice among newfamily planning acceptors at the Lamunti Community Health Center (UPT). This study used a quantitative,observational, and analytic design with a cross-sectional approach. The study was conducted at the LamuntiCommunity Health Center (Puskesmas) in May–June 2025. The study population was all new family planningacceptors who received family planning services during the study period. The sampling technique used totalsampling with 30 respondents. Partner support was measured using a structured questionnaire based on a Likertscale that included emotional, informational, instrumental support, approval, and involvement in decision-making.Data on contraceptive choice were obtained from family planning service records. Data were analyzed univariatelyand bivariately. The results showed that all respondents had a high level of partner support and all new familyplanning acceptors chose long-term contraceptive methods. The implant method was the most commonly chosenmethod, followed by the IUD. The lack of data variation in both variables prevented inferential statistical testsfrom being conducted. In conclusion, partner support plays a crucial role in creating a conducive environment forlong-term contraceptive choice. These findings emphasize the importance of a partner-based family planningcounseling approach in primary health care to improve the quality and sustainability of contraceptive use.